Bioaccumulation and Health Risk Assessment of Trace Elements in Oreochromis niloticus in Bukit Merah Lake, Malaysia - Mohd Ilman Che Abdullah,; Amir Shah Ruddin Md Shah,; Hazzeman Haris, (Tropical Life Sciences Research, 2022)
This study aims to determine the level of nine trace elements – As, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn in liver, gill and muscle of Oreochromis niloticus in Bukit Merah Lake (BML). The concentration of trace elements was measured using Inductively Coupled Plasma-Optical Emission Spectrometers (ICP-OES). Cd and Ni were found below the detection level, while Cr was only detected in gill and muscle tissues. The Metal Pollution Index (MPI) established were liver > gill > muscle. The ranking order of trace elements in the gills was Fe > Zn > Mn > Pb > As > Cu > Cr. For the liver, the ranking order was Fe > Cu > Zn > As > Mn > Pb, while in the muscle, the ranking order was Fe > Zn > Pb > As > Cu > Mn > Cr. The estimated daily intake (EDI) for all the trace elements in this study was calculated based on 168 g.day-1 of Malaysians’ fish consumption, indicating no potential risk. From the human health point of view, there was no significant non-carcinogenic risk of individual trace elements as evaluated by Target Hazard Quotient (THQ). As indicated by the Hazardous Index (HI), the cumulative effect of all trace elements also suggested no potential of non-carcinogenic risk. The carcinogenic risks assessed from Pb and As were also neglectable and there was no likelihood of getting cancer during one’s life span.